Epoxy resin with excellent ultraviolet resistance and mechanical properties derived from renewable camphoric acid. (16th May 2021) - Hu, Jingyuan; Wang, Chunhong; Dai, Jinyue; Teng, Na; Wang, Shuaipeng; Zhang, Liyue; Jiang, Yaming; Liu, Xiaoqing
Abstract: Generally, high‐performance epoxy resins, which are derived from aromatic compounds have two major disadvantages of yellowing and brittleness, and thus it presently remains a challenge for the facile synthesis of epoxy resin with excellent ultraviolet resistance and superior strength and toughness. Herein, a novel bio‐based epoxy resin diglycidyl ester of camphoric acid (DGECA) was synthesized from the renewable camphoric acid via an efficient and scalable route. The chemical structure of DGECA was carefully characterized by Fourier transform infrared (FT‐IR), nuclear magnetic resonance (NMR), and mass spectrometry before being cured with methylhexahydrophthalic anhydride (MHHPA). Compared with the cured diglycidyl ether of bisphenol A (DGEBA)/MHHPA, the cured DGECA/MHHPA system achieved 11.5%, 16.7%, and 109.4% increment in flexural strength (126 MPa vs. 113 MPa), modulus (2.8 GPa vs. 2.4 GPa), and impact strength (6.7 kJ/m 2 vs. 3.2 kJ/m 2 ), respectively. Moreover, cured DGECA exhibited extremely lower ultraviolet absorption (0.038A) and better ultraviolet resistance than that of cured DGEBA. This work provides a new strategy to synthesize epoxy resin with excellent ultraviolet resistance and high toughness by using the unique structure of renewable feedstock.